Assessing The Impact of Jajar Legowo Planting System on Wetland Paddy Productivity and Income of Farmers in Indonesia - Octavia Rizky Prasetyo; Kadir (Jurnal Ekonomi Dan Statistik Indonesia, 2023)
This study aims to assess whether Jajar Legowo planting system has a significant impact on increasing the productivity of wetland paddy and the income of the paddy growers in Indonesia. We applied a linear regression model to the results of the 2017 National Cost Structure of Paddy Cultivation Household Survey conducted by BPS-Statistics Indonesia in all 34 provinces. The main contribution of this study is to provide an evaluation of the performance of Jajar Legowo planting system in increasing paddy productivity and income of the farmers. Therefore, our research can be used by the government as a reference for future improvement of the implementation of Jajar Legowo cultivation system. Our findings show that the new cultivation system has a significant impact on increasing the productivity of wetland paddy. Without controlling for other variables affecting productivity, the estimation result pointed out that on average, the new cultivation system can increase productivity by about 10 per cent. However, after controlling for other variables (the farmers and other cultivations characteristics), the magnitude decreases to around 5 per cent. Moreover, our estimation results also show that the income of the farmers rises by around 12 per cent by implementing Jajar Legowo. Our study indicates that the implementation of Jajar Legowo planting system results in better efficiency than that of the conventional one.